Reconstruction of Creative History of Poem by M. Yu. Lermontov “They Loved Each Other for so Long and Dearly...” (1841) as a Way of Understanding the Meaning of Text - I. A. Kiselyova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
Dynamic poetics is analyzed - from draft to clean manuscript - the poem by M. Yu. Lermontov “They loved each other for so long and dearly ...” (1841), which is a free translation of the poem by H. Heine. Based on a comparison of the transcription of clean manuscript and two draft manuscripts of the poem, as well as the source - the German text - Lermontov’s creative process, his work on choosing the exact word and creating an integral artistic image is reconstructed. The article outlines the causes and mechanisms of Lermontov’s textual corrections that help to understand the movement of author’s thought. The process of Lermontov’s work on the text is associated with the emotional saturation of the “skeletal part” of a German source. Based on the textual analysis of the manuscripts of Lermontov’s poem from the “Notebook presented by V. F. Odoyevsky”, the semantic transformation of the source of the poem is traced, the process of enhancing the tragedy of the text achieved through its openness to eternity is revealed. The relevance of the problem is seen in the need to clarify the originality of the artistic imagery of Lermontov’s poem, to identify the reasons for the strength of its aesthetic impact on the reader, as well as the ontological meaning of the text. The semantic evidence of the text is revealed in the need for direct relations “here and now”, in understanding eternal life as a continuation of the mortal life. The novelty of the study has a factual (for the first time the creative process of composing a poem is presented in as much detail as possible) and interpretative in nature, associated with the refinement of Lermontov's worldview.